The Analysis of Reading Exercise in English Textbook Entitled Pathway to English for The SENIOR High School Grade X - anita sitompul; Jubil Sihite (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2019)
This study is aimed to analyze the types of Reading Exercises on the English textbook used by the first year students of SMA SWASTA METHODIST 7 Medan. The objective of the study is to find out the types of reading exercises on English textbook used by the first year students of SMA SWASTA METHODIST 7 Medan. The design of the study is descriptive qualitative research. The qualitative data were obtained by the steps that mentioned in the procedure of the research, i.e. reading, identification, classification and simplification. The researcher analyzed the exercise in three steps,identifying the topic, clutser the topic, draw explanation. The object of the study is the reading exercises created by Th. M. Sudarwati and Eudia Grace entitled by Pathway To English and published by Erlangga, 2017. The data was collected only by taking documentary analysis. It means that the writer document reading exercises on students’ English textbook and analyzed its types of reading exercises. The final result of this study shows that are five types of reading exercises on the English textbook they are Types of reading exercise are Matching Test, True/ False Reading Test, Multiple Choice item test, Completion item tests, and Long and Short answer questions. The result of reading exercise analysis shows that there are controlled exercise and guided exercise. In controlled exercises the researcher didn’t find exercise in Pathway to English textbook. And in guided exercises there are find in multiple choice in vocabulary 2 exercise. Matching cued word matching 3 exercise, matching picture cued sentence 1 exercise, vocabulary matching 5 exercise, matching selected response fill in vocabulary 7 exercise. True or false 3 exercise, completion item in the following of text 1 exercise, completion are in the text itself 9 exercise. In short answer question 6 exercise, long answer question 8 exercise. But, the researcher didn’t find exercise in multiple choice contextualized vocabulary / grammar and multiple choice vocabulary / grammar.